Recent advances in three‐dimensional bioprinting of stem cells. (14th May 2019) - Eswaramoorthy, Sindhuja D.; Ramakrishna, Seeram; Rath, Subha N.
Abstract: In spite of being a new field, three‐dimensional (3D) bioprinting has undergone rapid growth in the recent years. Bioprinting methods offer a unique opportunity for stem cell distribution, positioning, and differentiation at the microscale to make the differentiated architecture of any tissue while maintaining precision and control over the cellular microenvironment. Bioprinting introduces a wide array of approaches to modify stem cell fate. This review discusses these methodologies of 3D bioprinting stem cells. Fabricating a fully operational tissue or organ construct with a long life will be the most significant challenge of 3D bioprinting. Once this is achieved, a whole human organ can be fabricated for the defect place at the site of surgery. Abstract :